SINGLE VS. MULTIPLE ASSIGNMENT IN HUB-AND-SPOKE NETWORK: A TOTAL COST COMPARISON (Perner's Contacts, 2009)
The paper deals with total costs comparison of two hub location models – single and multiple allocation. The impact of inter-hub discount factor is examined on three different numerical examples.